Mortality and Morbidity in Infants <34 Weeks' Gestation in 25 NICUs in China: A Prospective Cohort Study - Jiang, Siyuan; Yan, Weili; Li, Shujuan; Zhang, Lan; Zhang, Yi; Shah, Prakesh S.; Shah, Vibhuti; Lee, Shoo K.; Yang, Yi; Cao, Yun (Frontiers in Pediatrics, 2020)
Objectives: To describe the rates and variability of mortality and morbidity of preterm infants born in China. Methods: This prospective cohort study included infants born at <34 weeks’ gestation and admitted to 25 NICUs within 7 days of birth between May 1st, 2015 and April 30th, 2016. Infants were followed until death or NICU discharge. The primary outcome was a composite of mortality or any major morbidity (sepsis, necrotizing enterocolitis, intraventricular /periventricular leukomalacia, retinopathy of prematurity, and bronchopulmonary dysplasia) in infants who received complete care following medical advice. Secondary outcomes included rate of discharge against medical advice, mortality and individual morbidities. Results: Of the 8065 infants, 6852 (85%) received complete care and 1213 (15%) were discharged against medical advice. Among infants who received complete care, the rate of the composite outcome was 27% (1827/6852), mortality 4% (248/6852), sepsis 14% (990/6852), necrotizing enterocolitis 3% (191/6550), intraventricular hemorrhage/ periventricular leukomalacia 7% (422/6307), retinopathy of prematurity 2% (67/3349), and bronchopulmonary dysplasia 9% (616/6852). There were significant variations between NICUs for all outcomes. Conclusions: Discharged against medical advice, mortality, and morbidity rates for preterm infants <34 weeks’ gestation are high in China with significant variations between NICUs.